Inside Cover: Chemodivergent Palladium‐Catalyzed Processes: Role of Versatile Ligands (ChemCatChem 23/2015). Issue 23 (December 2015) - Nava, Paola; Clavier, Hervé; Gimbert, Yves; Giordano, Laurent; Buono, Gérard; Humbel, Stéphane
Abstract : The Cover shows how the phosphinous acid–phosphinito catalyst (PAP‐Cat, top‐left of the picture) and the Herrmann–Beller catalysts (H‐B, bottom‐right) give rise to chemodivergent processes. In their Full Paper, P. Nava et al. combine experimental and computational approaches to understand the versatile role of the ligands. They show that PAP‐Cat can undergo a reversible proton shift. This proton shift helps to adapt the strength of the Pd−P bonds, in such a way that a stronger sigma donor (with a larger phosphinito nature) is always trans to the coordination site with the electronically poorer partner. This modulation of the trans effect is not possible with theH‐B catalyst.